Bioglass-based scaffolds coated with silver nanoparticles: Synthesis, processing and antimicrobial activity - Oliveira, Rodrigo L. M. S.; Barbosa, Lucas; Hurtado, Carolina R.; Ramos, Lucas de P. [UNESP]; Montanheiro, Thaís L. A.; Oliveira, Luciane D. [UNESP]; Tada, Dayane B.; Trichês, Eliandra de Sousa (Wiley, 2020)
Over the past few years, several tridimensional synthetic bone grafts, known as scaffolds, are being developed to overcome the autologous grafts limitations. Among the materials used on the production of scaffolds, the 45S5 bioglass stands out due to its capacity of bonding to hard and soft tissues. Silver nanoparticles are well-known for their antimicrobial properties and their incorporation on the scaffold may promote its antimicrobial response, avoiding microorganism proliferation on the materials surface. This study proposes a simple way to coat 45S5 bioglass-based scaffolds with silver nanoparticles. The scaffolds were obtained by the sponge replication technique and the silver nanoparticles were incorporated by soaking under ultrasonic stirring. The antimicrobial activity of the scaffolds was analyzed against three different microbial strains: S. aureus, P. aeruginosa, and C. albicans. Due to the heat treatment during the scaffold production, the bioglass crystalized mainly in a sodium calcium silicate phase, forming a glass–ceramic scaffold. The silver nanoparticles were coated in a well-distributed manner throughout the scaffold, while avoiding their aggregation. The coated scaffold inhibited the growth of all the analyzed microorganism. Therefore, the use of ultrasonic stirring to coat the bioglass scaffold with silver nanoparticles showed to be an efficient way to promote its antimicrobial response.
Keywords: 45S5 bioglass; antimicrobial scaffolds; glass–ceramic; silver nanoparticles; sponge replication technique